Ghanaian Newspapers Framing Of The First Female Vice-Presidential Candidate Of A Major Political Party In Ghana In The 2020 General Elections - Gyawu, B. (University Of Ghana, 2022)
This study examined the media framing of the first female Vice-Presidential candidate of a major political party in Ghana’s 2020 general elections. Specifically, the study examined the prominence, gender stereotypes in media reporting and the framing of stories related to the candidate. The quantitative content analysis was employed in conjunction with a coding guide to gather stories related to the candidate in the Daily Graphic and Daily Guide newspapers. Guided by the framing and liberal feminists’ theories, findings suggest variation in the frequency of reporting of the first female Vice-Presidential candidate in the two newspapers. While the Daily Graphic provided greater coverage, the Daily Guide lagged in reporting on the candidate. Additionally, stories on the first female Vice-Presidential candidate were mostly placed on pages other than the front page, back page, and center page, with most stories having positive gender stereotypes. Significantly, male reporters covered more stories on the candidate than their female counterparts. The study concluded that women politicians receive less coverage during elections and their stories less prioritized on prominent pages by Ghanaian newspapers. The study recommended that the Ghanaian media, particularly the print media, increase their coverage of female politicians during any general elections. The study also proposed that Ghanaian media outlets and practitioners step up efforts to combat gender inequality through increased public awareness and the design of gender transformative programmes that seek to promote gender transformative change at the individual, societal, and systemic levels across all spheres of life, particularly in the political arena.
M.A. Communication Studies
Keywords: Ghanaian Newspapers; First Female Vice-Presidential Candidate; Ghana; 2020 General Elections